The position of the EU in the semiconductor value chain: Evidence on trade, foreign acquisitions, and ownership - Andrea Ciani; Michela Nardo (European Commission, 2022)
We map companies belonging to the semiconductor value chain at the world level and investigate the turnover of the companies by jurisdiction of their ultimate owner. Total turnover for the top-10 companies, with respect to revenue, among the manufacturers of semiconductors amounts to 266 Billion EUR for year 2020. The same group of companies accounts for 87% of market capitalization of this industry in 2021. Our coverage is uneven across jurisdictions. We have a richer coverage for Europe than for the US and China, given the interest in analysing the European landscape. Data on turnover by segment shows that EU-owned companies represent a relevant share of the input suppliers for the production of semiconductors (evidence confirmed by De Jong, 2020, as well as by Kleinhans and Baisakova, 2020). Indeed EU companies are among the largest suppliers of chemicals and gases in this supply chain, accounting for 34% of world turnover in 2020. US companies are leaders in the production of equipment used for the production of semiconductors with 31% of the turnover, closely followed by European ones with 27%. The picture changes when looking at the turnover of EU-owned chip producers (foundries) and chip designers (fabless companies), which is negligible. Taiwanese firms share with South Korean manufacturers the leadership in the foundry segment.
Keywords: 330